Severe Oral Mucosal Ulceration Associated with Oral Bisphosphonate Use: The Importance of Imparting Proper Instructions on Medication Administration and Intake - Manju Chandran; Wanling Zeng (Case Reports in Medicine)
Oral bisphosphonates are approved for the treatment of bone loss associated with several conditions including postmenopausal osteoporosis. Although generally well tolerated, adverse effects such as gastroesophageal reflux and oesophageal and peptic ulceration may occur. Oral mucositis and ulceration are lesser-known side effects. Proper counselling and rigorous adherence to the administration instructions are crucial. We describe a case of bisphosphonate-induced severe oral mucosal ulceration in an elderly woman that was caused by incorrect instructions and/or incorrect understanding of instructions for oral alendronate intake.